Physiotherapist-delivered cognitive behavioural interventions are effective for low back pain, but can they be replicated in clinical practice? A systematic review - Hall, A; Richmond, H; Copsey, B; Hansen, Z; Williamson, E; Jones, G; Cooper, Z; Lamb, S (Taylor and Francis, 2016)
Purpose: To determine if physiotherapist-led cognitive-behavioural (CB) interventions are effective for low back pain (LBP) and described sufficiently for replication. Method: RCTs of patients with LBP treated by physiotherapists using a CB intervention were included. Outcomes of disability, pain and quality of life were assessed using the GRADE approach. Intervention reporting was assessed using the Template for Intervention Description and Replication. Results: Of 1898 titles, 5 RCTs (n=1,390) were identified. Compared to education and/or exercise interventions, we found high quality evidence that CB had a greater effect (SMD; 95% CI) on reducing disability (-0.19; -0.32, -0.07), pain (- 0.21; -0.33, -0.09); and moderate quality evidence of little difference in quality of life (-0.06; -0.18 to 0.07). Sufficient information was provided on dose, setting and provider; but not content and procedural information. Studies tended to report the type of CB component used (e.g. challenging unhelpful thoughts) with little detail on how it was operationalised. Moreover, access to treatment manuals, patient materials and provider training was lacking. Conclusions: With additional training, physiotherapists can deliver effective CB interventions. However, without training or resources, successful translation and implementation remains unlikely. Researchers should improve reporting of procedural information, provide relevant materials and offer accessible provider training.